2017
DOI: 10.1002/cam4.1241
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CD133+CD54+CD44+ circulating tumor cells in colorectal cancer with liver metastasis

Abstract: In the previous study, we had showed the expression of CD133+ CD54+ CD44+ cellular subpopulation of circulating tumor cells (CTCs) was significantly associated with liver metastasis of colorectal cancer (CRC). This study aimed to explore whether this subpopulation of CTCs have a prognostic value in CRC patients. Flow cytometry was used to detect the expression of cellular subpopulations of CTCs with CD133, CD54, and CD44 in 152 CRC patients, between December 2013 and October 2014. The impact of clinicopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Interestingly, the Warburg effect and the enhancement of the PPP in CSCs seem to be responsible for the enhanced production of antioxidant molecules and the overall reduction of reactive oxygen species (ROS) demonstrated in vivo and in vitro models (15,55,59). CD44 (CD44v) expression in CSCs suppresses PKM2 (mice model), thereby decreasing pyruvate dehydrogenase activity and promoting PPP; these are all consistent with the stabilization of the cysteine/glutamate antiporter and elevated GSH levels (58,(60)(61)(62). All these lead to higher survival rates of CSC even in hostile environments (15,57,58).…”
Section: Metabolism Characteristics Of Csc That Enhance Invasivenessmentioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the Warburg effect and the enhancement of the PPP in CSCs seem to be responsible for the enhanced production of antioxidant molecules and the overall reduction of reactive oxygen species (ROS) demonstrated in vivo and in vitro models (15,55,59). CD44 (CD44v) expression in CSCs suppresses PKM2 (mice model), thereby decreasing pyruvate dehydrogenase activity and promoting PPP; these are all consistent with the stabilization of the cysteine/glutamate antiporter and elevated GSH levels (58,(60)(61)(62). All these lead to higher survival rates of CSC even in hostile environments (15,57,58).…”
Section: Metabolism Characteristics Of Csc That Enhance Invasivenessmentioning
confidence: 89%
“…It is known that glutamine metabolism regulates the sensitivity of CSCs to metformin via the AMPK-mTOR pathway (76). Furthermore, glutamine can be hydrolyzed to glutamate which can be used to produce GSH (60)(61)(62).…”
Section: Metabolism Characteristics Of Csc That Enhance Invasivenessmentioning
confidence: 99%
“…In a recent study, flow cytometry showed that the liver metastatic CRC patients with high expression of CD133 + CD54 + , CD133 − CD54 + , and CD133 + CD44 + CD54 + cellular subpopulations of circulating tumor cells had a worse survival than those patients with low expression. Moreover, the cellular subpopulation expressing CD133 + CD44 + CD54 + of CTCs showed its proficiency as independent prognostic factors for survival in CRC patients with liver metastasis not treated with surgical approach [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study of MICs phenotype is particularly important for the understanding of the biological mechanism of metastasis and could also potentially harbor prognostic and predictive significance. In a recent study, the CD133 + CD44 + CD54 + subpopulation of CTCs has a prognostic value in metastatic colorectal cancer and shows a significant survival improvement in patients who did not undergo surgical treatment for metastasis [ 65 ]. Those studies are particularly promising, considering the feasibility of this test (a simple blood sampling) potentially able to add more prognostic information at subsequent moments during patient monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for potential CTC detection were based on FSC (physical properties of the cells) and pan-cytokeratin (intracellular epithelial marker). Second, we also used DAPI as a marker to select nucleated cells and FSC and SSC to remove all possible contamination by debris as suggested by previous studies (32,33), thus improving the sensitivity and specificity of CTC detection. Last, we added VIM to the panel for CTC detection.…”
Section: Discussionmentioning
confidence: 99%